Creatinine clearance and 24-hour creatinine excretion profile in the urine of people after physical exercises - Bakonska-Pacon, E. (Biology of Sport, 2006)
Physical exercise is one of the factors disturbing organism homeostasis which can be seen in the urine composition owing to the changes in the hemodynamic and metabolic processes in the kidneys. The aim of the study was the evaluation of the influence of physical exercise on the blood serum and urine creatinine concentration in the 24-h urine collection and on creatinine clearance. The study was also to prove the applicability of creatinine concentration in the urine as a reference parameter for other biochemical indices determined in the post-exercise urine. The group under study comprised 7 students. The 24-h urine collection was carried out in the group of students twice with an interval of three weeks. During the first 24-h collection (test 1) students performed the progressive test on the cycloergometer. The second 24-hour collection (test 2) was taken during a routine physical activity and the subjects were free of strain. The material for the tests was the urine collected during 24 h and the blood collected from the vein three times in test l: pre-exercise, immediately after the exercise and after 24 h in test 2 - once in the morning on the completion of the urine collection. The urine creatinine was determined by means of the colorimetric method, the serum creatinine concentration was determined in a biochemical analyzer BioMerieux. In the blood taken after exercise and at rest the lactate concentration was estimated by the Dr Lange test. Endogenic creatinine clearance (ml/min/l.73 m2 body surface) was also calculated. The differences in creatinine concentrations in the urine in the test with exercise were only by 7.7% higher and were negligible. However, creatinine concentration in the blood serum in the same test was by 13 per cent higher and this difference was at the significance level p<0.05. Creatinine concentration increase in the serum was due to post-exercise reduction in plasma volume (%deltaPV=-11.75%±4.77). Also the 24-h urination was similar in both tests. Creatinine clearance values expressed in ml per min per l .73m2 of body surface are lower in test l (exercise) than creatinine clearance values in test 2 (at rest); individual differences do not exceed 9%. With the obtained results, it can be said that a moderate physical effort does not disturb the Filtration function of glomerula,